(untitled) (AYUSHDHARA, 2020)
Childbirth is a physiologic and natural process has been undertaken by women over the years with professional assistance in which most of the women experience labour pain and childbirth as most severe and agonising event of a woman’s existence. Labour is linked with a painful experience, though there are no underlying pathological processes, a lot of women are worried about labour pain and how they can be relieved of pain. Pharmacological agents such as pethidine (Meperidine) and other analgesics are used to effectively control labour pain. Both pharmacological and non-pharmacological approaches are necessary to relief labour pain effectively. Some women employ other non- pharmacological pain relief measures during labour such as breathing exercises, taking showers, and assuming specific positions and moving about to control their pain. In addition, the use of herbal medicine has been reported to relieve labour pain. Description of labour in Ayurvedic science, though found since 5000yrs ago is a very less known concept to many people as they are not much in practice. Currently the labour is managed only by the conventional medicine with some interventions with addition of Yoga and Ayurveda in the Antenatal care. By evaluating the complete knowledge of Prasava or the labour explained in Ayurvedic science, the same may be incorporated as an add-on in the future studies to make it evidence based and also to corroborate the authenticity of the science through research.